Use of ICTs for Teaching-learning Oral Communication During the Pandemic - Casano, Leyla (2022)
In this study, the main objective is to systematize a teaching experience in the development of oral communication competence with the use of ICTs. This study applied a qualitative approach, documentary in scope, and is structured based on the method of systematization of educational experience. Two techniques were used: documentary review and reconstruction of experience from memory. The results on the course improvements were promising: 89.48% of students were satisfied with the applied proposal and 92.95% with teaching performance. We conclude that including ICT in the teaching-learning process facilitates the development of oral competence in university students and requires the active participation of the instructor.